Effect of Psychotherapy on Reduction of Fear of Childbirth and Pregnancy Stress: A Randomized Controlled Trial - Abdollahi, Somayeh; Faramarzi, Mahbobeh; Delavar, Mouloud Agajani; Bakouei, Fatemeh; Chehrazi, Mohammad; Gholinia, Hemmat (Frontiers in Psychology, 2020)
Introduction: The fear of childbirth (FOC) has an adverse effect on the physical and mental health of pregnant women and increases the adverse maternal and fetal outcomes. Previous research reported the effect of psychological interventions such as cognitive behavioral therapy, relaxation therapies, and short-term psycho-educational intervention on FOC. We examined whether adding MI psychotherapy to prenatal care usual (PUC) is superior to PUC alone to reduce the scores of fear of child birth, pregnancy stress, and self-efficacy. Material and methods: An RCT with two-arm parallel group, 1:1 allocation ratio assigned 70 pregnant women (aged 18-50) attending public health centers in an education hospital, Iran, to receive five sessions of group MI psychotherapy plus PUC (N=35), or to receive PUC alone (N=35). The primary outcomes were the FOC scores (Wijma Delivery Expectancy /Experience Questionnaire-WDEQ), pregnancy-specific stress (Prenatal Distress Questionnaire-NUPDQ), the anxiety (Spielberger state-anxiety), the Child birth self-efficacy index (CBSI), at 5 weeks post-randomization. Additional measures included subscales of the WDEQ and the NUPDQ, patients’ compliance, and satisfaction with psychotherapy intervention, at 5 weeks post-randomization as a secondary outcome. Main Results: The post-trial results indicated that the outcome scores diminished more considerably in psychotherapy than in the PUC for total FOC scale with a large effect size (B=-23.54, p=<0.001, η2= 0.27), for total pregnancy stress with a large effect size (B=-4.51, p=<0.001, η2= 19), and for state-anxiety with a large effect size (B=-12.42, p=<0.001, η2= 0.22). However, the score of self-efficacy and concern about physical symptoms did not differ between psychotherapy and PUC groups (P<0.05). Discussion: Adding 5 weeks of group psychotherapy to prenatal usual care could be considered as an adjunctive care option for reducing FOC, pregnancy stress, and general anxiety in pregnant women in the third trimester. Future research may focus on sustaining the effects and evaluating the economic impacts of adding the psychotherapy to PUC.